Experimental and numerical research on axial compression performance of precast concrete columns with a novel steel connection - Guo, Jinlong; Li, Chao; Chen, Min; Guo, Yanfei; Fu, Qiang; Li, Yongjin (Frontiers in Materials, 2025)
To investigate the axial compression performances of precast concrete columns with a novel steel connection, axial compression tests were carried out on 14 specimens. The effects of four different forms of the steel connections on the failure modes and axial compression performance of the specimens were studied, respectively. Furthermore, the influences of the cross-sectional area and the anchorage length of the steel connections on the specimens were explored. The columns with both studs and anchor plates exhibit good axial compression stiffness, bearing capacity, and ductility. For specimens with neither studs nor anchor plates on the steel connection, the yield loads decrease by 1.8%–5.2%. Increasing the cross-sectional area of the steel connection can significantly improve the axial compression bearing capacity of the columns, but has a negligible effect on the initial axial compression stiffness. Within the range of cross-sectional dimensions discussed in this test, the yield load has increased by up to 31.5%. In addition, a verified numerical model of the column was established and further analysis was conducted. The studs and anchor plates can effectively ensure that the steel connections are well anchored in the concrete under axial compression. For the column with both studs and anchor plates, the exposed steel connection serves as the axial compression control section, and the failure of the column under axial compression is the compressive yield of the steel connection. Lastly, the axial compressive bearing capacity of the column was calculated by the equation.